Genosensor based on a nanostructured, platinum-modified glassy carbon electrode for Listeria detection - Kashish; Gupta S.; Dubey S.K.; Prakash R. (My University, 2025)
In this article, we describe the development of a simple and cost-effective genosensor probe based on a glassy carbon electrode modified with platinum nanomaterials dispersed in a chitosan matrix. Further, this probe was explored for the label-free detection of Listeria monocytogenes obtained from milk samples. DNA-based interfacial interaction between target DNA and platinum nanomaterials (PtNPs) immobilized with 24 mer ssDNA was investigated using impedance spectroscopy. As-prepared nanomaterials (for electrode fabrication) were characterized by UV-vis, FT-IR, TEM and cyclic voltammetry before fabricating the impedimetric sensor platform. The interfacial interaction between PtNPs and DNA results in the increase of charge transfer resistance (RCT) on hybridization with consecutive increasing concentrations of target DNA. This user-friendly and simple platform was used for the detection of target DNA and shows excellent response and specificity (even for 1-bp mismatch of target DNA). Also, this sensing platform was utilized for the detection of Listeria monocytogenes in real samples (milk beverage) and had a wide range of detection from 1 × 10-12 M to 1 × 10-4 M. In general, our simple and user-friendly sensor probe shows potential for detection of Listeria monocytogenes in food samples with high specificity. © The Royal Society of Chemistry 2015.